PENDEKATAN INKUIRI BERBASIS ETNOMATEMATIKA: ANALISIS KEMAMPUAN BERPIKIR KREATIF MATERI BANGUN DATAR - Novitasari Novitasari; Elly Anjarsari; Erra Noer Rohmania Aishwaray; Rahma Febriyanti; Rayinda Aseti Prafianti (IKIP Siliwangi, 2023)
Creative thinking is one of the most important aspects of learning, with creative thinking students can develop their abilities in every material being taught. This study aims to describe students' creative thinking skills in learning using an ethnomathematical-based inquiry learning model on two-dimensional figure. This research is a qualitative descriptive study. The subjects of this study were 9th grade students of junior high school, which amounted to 15 people. Data collection techniques used in the form of test-based interviews and questionnaires. The data obtained were then analyzed using data analysis techniques with the stages of condensing data, data display, and conclusions drawing. The results showed that each group had different levels of creative thinking ability. The results of this study indicate that each group has a different level of creative thinking ability. There are two groups that have the ability to think creatively at level 3 (creative) which is indicated by the fulfillment of two components of creative thinking ability, namely fluency and flexibility. Meanwhile, one other group has a level of creative thinking ability in the quite creative category (level 2) which only fulfills one component of creative thinking ability, namely flexibility.